COMMUNICATION WITH THE OUTSIDE WORLD ONLY BY FACIAL EXPRESSIONS, A CLINICAL CASE OF AMYOTROPHIC LATERAL SCLEROSIS IN A YOUNG WOMAN - Rasulova Dilbar Kamoliddinovna; Rasulova Munisa Bahtiyarovna (Scholar Express Journals, 2023)
ALS takes away the ability to move, speak, write, print - but does not take away the need to express feelings, emotions and desires. ALS kills the motor neurons in the brain and spinal cord that send signals to different muscle groups. Amyotrophic lateral sclerosis can occur both in the elderly and at a younger age. Given the rarity of the disease at a young age, we decided to highlight the clinical case of ALS in a young woman who communicated with the outside world only through facial expressions. With careful care and timely diagnosis of ALS, despite being bedridden, patients have a survival rate of more than 5 years.
Keywords: neurodegenerative disease; amyotrophic lateral sclerosis; bulbar disorderrs; facial expressions